Palmitate increases L-type Ca2+ currents and the size of the readily releasable granule pool in mouse pancreatic beta-cells. - Olofsson, C; Salehi, A; Holm, C; Rorsman, P (2004)
We have investigated the in vitro effects of the saturated free fatty acid palmitate on mouse pancreatic beta-cells by a combination of electrophysiological recordings, intracellular Ca(2+) ([Ca(2+)](i)) microfluorimetry and insulin release measurements. Addition of palmitate (1 mm, bound to fatty acid-free albumin) to intact islets exposed to 15 mm glucose increased the [Ca(2+)](i) by approximately 30% and insulin secretion 2-fold. Palmitate remained capable of increasing [Ca(2+)](i) and insulin release in the presence of tolbutamide and in islets depolarized by high K(+) in combination with diazoxide, indicating that the stimulation occurs independently of closure of ATP-regulated K(+) channels (K(ATP) channels). Palmitate (0.5 mm) augmented exocytosis (measured as an increase in cell capacitance) in single beta-cells and increased the size of the readily releasable pool (RRP) of granules 2-fold. Whole-cell peak Ca(2+) currents rose by approximately 25% following addition of 0.5 mm palmitate, an effect that was abolished in the presence of 10 microm isradipine indicating that the free fatty acid specifically acts on L-type Ca(2+) channels. The actions of palmitate on exocytosis and Ca(2+) currents were not mimicked by intracellular application of palmitoyl-CoA. We conclude that palmitate increases insulin secretion by a K(ATP) channel-independent mechanism exerted at the level of exocytosis and that involves both augmentation of L-type Ca(2+) currents and an increased size of the RRP.